The Mediating Role of the Self-Concept Between the Relationship of the Body Satisfaction and the Intention to Be Physically Active in Primary School Students - Sánchez-Miguel, Pedro Antonio; León-Guereño, Patxi; Tapia-Serrano, Miguel Angel; Hortigüela-Alcalá, David; López-Gajardo, Miguel A.; Vaquero-Solís, Mikel (Frontiers in Public Health, 2020)
The aim was to analyze the extent to which anthropometric values, in line with body image and physical ability, predict physical self-concept, and the latter, in turn, predicts the practice and intention to pursue physical activity. A total of 302 participants, 150 males and 152 females were recruited from different primary schools in Extremadura (Spain). The age of the participants ranges from 10 to 13 years old (M = 11.74; SD = 0.86). The indirect effects of the model showed significant relationship between physical condition (p = 0.001) and PA levels, according to the perception of self-concept [β = 0.231, 95% BcCI = (0.055, 0.212)]. However, anthropometric variables proved not to be related to any significant extent (p < 0.05). The second level covered the indirect effects between the intention to be physically active and self-concept, which showed a significant relationship between the perception of self-concept (p = 0.000) and the intention to be physically active. Last, the third level showed significant relationships between physical condition (p = 0.001) and the intention to pursue physical activity. The present investigation concluded that physical condition, anthropometric variables, and body image predict the perception of physical self-concept in adolescents. Finally, this article highlights the importance of body image perception, anthropometric values, and physical condition in the intention of being physically active. In addition, it highlights the mediating role of physical self-concept to develop physical activity.